The Effect of WhatsApp Application Usage on Student Achievement in Business-based Subjects - Zainol, Zuraidah; Mohd Samingin, Nursyafiqah (International Business Education Journal, 2022)
Although online learning has been highlighted as a solution to continue the teaching and learning process since the whole world was hit by the Covid-19 pandemic, there is criticism that students in Malaysia are not yet ready to pursue online learning and may only contribute to the decline in students’ academic achievement. Hence, to assess the relevance of online learning towards student achievement, this study aimed to determine the relationship between the use of WhatsApp applications (usability, engagement, and attitude) and student achievement in online learning, and the influence of the use of WhatsApp apps (usability, engagement, and attitude) on students’ achievement in business-based subjects. The study employed a quantitative approach. A total of 210 respondents, comprising Form 4 students from selected schools in Ipoh Perak, were involved in this study. To collect data, questionnaires were used as instruments. The study data were analysed using Pearson correlation and multiple regression analysis. The findings of the Pearson correlation analysis showed a significant and negative relationship between engagement in the use of the WhatsApp app and the achievement of online learning. The findings of the regression analysis also found that engagement in the use of WhatsApp apps influenced the achievement of online learning, but not for the usability and attitude towards the use of the WhatsApp app. The influence of engagement in the use of the WhatsApp app on the achievement of online learning is negative, indicating that the greater the engagement with the WhatsApp app, the more students’ achievement declines. Therefore, the findings reveal that even though the WhatsApp app could be one of the aids in online learning, excessive use of it can reduce students’ achievement.